A mobile and web-based security guard patrolling, monitoring and reporting system to maintain safe and secure environment at premises - Gannapathy, Vigneswara Rao; Narayanamurthy, Vigneswaran; Md Isa, Ida Syafiza; Subramaniam, Siva Kumar; Tuani Ibrahim, Ahamed Fayeez; Rajkumar, Sujatha (International Association of Online Engineering, 2023)
The guard tour system helps companies and organizations to monitor their security activities such as protecting people, buildings, assets, or equipment. According to the existing system, the patrolling at each checkpoint is being executed by using RFID-based digital data loggers that records and save all patrolling entries internally. The data will be transferred manually by the guard once the patrolling is completed. In some cases, when there is a problem with the device, the system unable to retrieve the patrolling data that has been already stored in the device. In addition, the current system also not be able to track the guard’s movement, patrolling information, and incidents in real-time basis. The main aim of this work is to develop a Security Guard Patrolling, Monitoring and Reporting (eSmartGuard) system that able incorporates many unique and intelligent technologies such as NFC, GPS and IoT to records and save the patrolling data automatically on the cloud/server in real-time basis. An important value-added feature of the system is real-time incidents notification that able to notify any risk of the guards instantly to the security officers. Furthermore, through the eSmartGuard, the patrolling information such as date, time, GPS coordinate, guard ID can be monitored and retrieved remotely via proposed Mobile Apps and Web at a convenient time. The eSmartGuard patrolling system is proposed to improve the safety of the people and assets by assisting the security guards to perform their patrolling duty efficiently.